Laparoscopy in inguinal hernia and complete androgen insensitivity syndrome in children. Whether and when to remove the gonads because of cancer? - Wolak, Przemysław (Medical Studies/Studia Medyczne, 2015)
Androgen insensitivity syndrome (CAIS) – also called Morris syndrome, formerly known as testicular feminisation syndrome – is a congenital disorder of sex development caused by various mutations in the gene encoding the androgen receptor. Androgen insensitivity syndrome occurs in a complete form (complete androgen insensitivity syndrome – CAIS) or a partial form (partial androgen insensitivity syndrome – PAIS). In approximately 1% (according to various researchers, 0.8–2.4%) of cases of inguinal hernia in girls during the time before menarche, CAIS is seen. The laparoscopic procedure for inguinal hernia repair allows a visual assessment of the gonads, and possibly the collection of specimens from the gonads. This is much simpler, compared to the conventional procedure.